Ordinance no. 1, § 6, THE MINING ECHO, Jul. 7, 1877 at 1 (Empire City, Kansas). - (:unkn) unknown (General Publisher, 1870)
Any person who shall carry any concealed pistol, dirk, or other deadly weapon, within the limits of thi- city, shall he deemed guilty of a misdemeanor, and upon conviction thereof, be fined in a sum not less than $10 nor more than $50.
--
Keywords: CARRY - CONCEALED